2006
DOI: 10.4314/sajhe.v19i6.25552
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to predictive studies: Possibilities and challenges

Abstract: This article investigates methodological issues associated with predictive studies related to selection and access to Higher Education. These issues are discussed in the context of tests designed and administered by the Alternative Admissions Research Project (AARP) at the University of Cape Town. The aim of the project is to design tests that broaden access to talented students who are not easily identified through the High School Senior Certificate examination system. The tests attempt to provide a mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…(Gadamer, 2003, p. 295). 7 Similar performance patterns are evident in other studies recently conducted at UCT (Cliff, Yeld, & Hanslo, 2003;Visser and Hanslo, 2005;Scott, Hendry, Jawitz, & Gibbon, 2005) and they are supported by preliminary patterns of 'racially' differentiated throughput performance across the higher education system (Scott et al, 2005). policy and the decreased performance.…”
Section: An Alternative Readingsupporting
confidence: 73%
“…(Gadamer, 2003, p. 295). 7 Similar performance patterns are evident in other studies recently conducted at UCT (Cliff, Yeld, & Hanslo, 2003;Visser and Hanslo, 2005;Scott, Hendry, Jawitz, & Gibbon, 2005) and they are supported by preliminary patterns of 'racially' differentiated throughput performance across the higher education system (Scott et al, 2005). policy and the decreased performance.…”
Section: An Alternative Readingsupporting
confidence: 73%
“…For the ESL students the weakening correlation between their incoming January PTEEP scores, their mid-year results and their final results seems shows the Geography extended degree module helped the very students it is designed to. Visser andHanslo (2005, 1162) found that 'academic development programmes and course interventions may have impacted positively on the performance of weak incoming students and this serves to further depress the correlation co-efficient when correlating testing instrument scores with course performance scores', thus, a weak correlation can be taken as proof of academic intervention. In terms of English language proficiency, the South African Senior School Higher Grade…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Initially, there was no nationally accepted valid and reliable test which assessed academic potential, making admissions and placement management very difficult (Visser and Hanslo 2005;Van der Merwe and De Beer 2006). Thus, a placement test, commonly known as the PTEEP test, was developed by the Alternative Admissions Research Project (AARP) as an 'assessment tool which endeavours to widen access into the University of Cape Town [by identifying] educationally talented students with the potential to succeed' (Visser andHanslo 2005, 1161). The PTEEP was extensively tested (for more than a decade) and was recognised by UCT as a valid predictor of academic success.…”
Section: The Placement Test In English For Educational Purposes (Pteementioning
confidence: 99%
See 1 more Smart Citation
“…What society expects and government pays for, in South Africa at least, are graduates (Visser and Hanslo 2005).…”
Section: Introductionmentioning
confidence: 99%